Phenomenally Affective: Kass Morgan’s The 100 and the Apocalyptic Politics of Care - Hannah Nelson-Teutsch (Current Objectives of Postgraduate American Studies)
This essay confronts a growing consensus that the apocalyptic mode is the wrong way to tell the story of climate change. Contrary to the widely held belief that an apocalyptic framework invites apathy and political disengagement, I contend that the apocalyptic mode can in fact serve as a vital locus of highly differentiated and deeply felt engagements with the embodied experience of dwelling in crisis. An ecocritical reading of what I term ‘phenomenal apocalyptic narratives’—like Kass Morgan’s The 100, which I will explore in detail—reveals an impulse to care that is avowedly political in nature.